Disambiguating will-conditionals - Ciardelli, Ivano; Ommundsen, Adrian (Proceedings of the Amsterdam Colloquium, 2022)
We bring together two ideas that are widely accepted in the literature: (i) conditionals with modal consequents are systematically ambiguous between a reading on which the if-clause restricts the modal, and a reading on which the if-clause introduces an epistemic supposition and the modal is unrestricted; (ii) ‘will’ is a modal. Together, (i) and (ii) imply that ‘will’-conditionals are systematically ambiguous between a reading as restricted historical claims, and one as unrestricted historical claims made under a supposition. We argue that this prediction is correct and that the existence of the relevant ambiguity has far-reaching repercussions for several important debates concerning conditionals.